2019
DOI: 10.1186/s12887-019-1399-5
|View full text |Cite
|
Sign up to set email alerts
|

“From the moment I wake up I will use it…every day, very hour”: a qualitative study on the patterns of adolescents’ mobile touch screen device use from adolescent and parent perspectives

Abstract: BackgroundThe use of mobile touch screen devices, e.g. smartphones and tablet computers, has become increasingly prevalent among adolescents. However, little is known about how adolescents use these devices and potential influences on their use. Hence, this qualitative study explored adolescents’ perceptions on their patterns of use and factors influencing use, and perceptions and concerns from parents.MethodsSemi-structured interviews were conducted with adolescents (n = 36; 11 to 18 years) and their parents/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
51
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 49 publications
10
51
0
2
Order By: Relevance
“…In this qualitative study, adolescents provided rich descriptions about their daily screen-based routines, providing insights into the nature, patterns, perceptions and to the multiple functions that these devices offer. In line with previous literature, 23 we showed that adolescents' use these devices to carry out several social (e.g., communicating with friends), functional (e.g., setting an alarm) and recreational tasks (e.g., streaming videos). Moreover, smartphones offer persistent access to the internet, offering limitless opportunities to remain connected via digital communication.…”
Section: Discussionsupporting
confidence: 91%
“…In this qualitative study, adolescents provided rich descriptions about their daily screen-based routines, providing insights into the nature, patterns, perceptions and to the multiple functions that these devices offer. In line with previous literature, 23 we showed that adolescents' use these devices to carry out several social (e.g., communicating with friends), functional (e.g., setting an alarm) and recreational tasks (e.g., streaming videos). Moreover, smartphones offer persistent access to the internet, offering limitless opportunities to remain connected via digital communication.…”
Section: Discussionsupporting
confidence: 91%
“…Studies have been correlational and based heavily on self-report. Self-reporting may be particularly problematic as it relates to screen time use as adolescents often multi-task in their screen time use (eg, scrolling phone-based social media while doing homework on a laptop) 102. This brief, unplanned, and dynamic nature of screen time may hamper adolescents’ ability to estimate their use.…”
Section: Processes Impacting Energy Expenditurementioning
confidence: 99%
“…Concretamente, destacan la meteorología (excepto los chicos muy activos), los conflictos, la falta de espacio, la falta de infraestructuras para el juego o una nueva barrera encontrada, el uso de medios tecnológicos. Y es que un reciente estudio que analiza el uso del móvil en la adolescencia advierte que este es elevado, frecuente y ubicuo y se caracteriza por una comprobación constante del aparato, pudiendo realizar múltiples tareas durante su uso, siendo los recreos uno de los espacios donde normalmente se utiliza (Toh, Howie, Coenen, & Straker, 2019).…”
Section: Discussionunclassified